2018
DOI: 10.1038/s41598-018-29859-9
|View full text |Cite
|
Sign up to set email alerts
|

Robust increase of leaf size by Arabidopsis thaliana GRF3-like transcription factors under different growth conditions

Abstract: An increase in crop yield is essential to reassure food security to meet the accelerating global demand. Several genetic modifications can increase organ size, which in turn might boost crop yield. Still, only in a few cases their performance has been evaluated under stress conditions. MicroRNA miR396 repress the expression of GROWTH-REGULATING FACTOR (GRF) genes that codes for transcription factors that promote organ growth. Here, we show that both Arabidopsis thaliana At-GRF2 and At-GRF3 genes resistant to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…The growth and development processes are driven by hormonal signaling pathways that are fundamental in the response to submergence and drought in plants [ 41 ], where transcription factors and miRNAs participate. Several differentially expressed miRNAs identified in this work are known to act over target genes encoding transcription factors such as miR156 (squamosa promoter-binding protein like, SPL) [ 42 , 43 , 44 ], miR159 (giberellic acid-MYB transcription factor, GAMYB [ 28 , 29 ]), miR164 (NAM-ATAF-CUC domain transcription factor NAC, MYB [ 45 ]), miR166 (basic leucine zipper transcription factor, HD-ZIP III [ 46 , 47 ]), miR167 (auxin-responsive factor, ARF [ 30 , 35 , 48 ]), miR169 (nuclear transcription factor Y subunit alpha, NFYA [ 49 , 50 , 51 , 52 ]), miR319 (teosinte branched1/cycloidea/proliferating cell nuclear antigen factor, TCP [ 53 ]), and miR396 (growth-regulating factor, GRF [ 54 , 55 ]). Other target genes predicted in this study are listed in Table S6 .…”
Section: Discussionmentioning
confidence: 99%
“…The growth and development processes are driven by hormonal signaling pathways that are fundamental in the response to submergence and drought in plants [ 41 ], where transcription factors and miRNAs participate. Several differentially expressed miRNAs identified in this work are known to act over target genes encoding transcription factors such as miR156 (squamosa promoter-binding protein like, SPL) [ 42 , 43 , 44 ], miR159 (giberellic acid-MYB transcription factor, GAMYB [ 28 , 29 ]), miR164 (NAM-ATAF-CUC domain transcription factor NAC, MYB [ 45 ]), miR166 (basic leucine zipper transcription factor, HD-ZIP III [ 46 , 47 ]), miR167 (auxin-responsive factor, ARF [ 30 , 35 , 48 ]), miR169 (nuclear transcription factor Y subunit alpha, NFYA [ 49 , 50 , 51 , 52 ]), miR319 (teosinte branched1/cycloidea/proliferating cell nuclear antigen factor, TCP [ 53 ]), and miR396 (growth-regulating factor, GRF [ 54 , 55 ]). Other target genes predicted in this study are listed in Table S6 .…”
Section: Discussionmentioning
confidence: 99%
“…The contradiction may be comprehensible in light of an additional function of AtGRFs in the root: ectopic AtGRF expression interferes with the normal patterning of cell divisions in the stem cell niche and organization of the quiescent center (QC). Nevertheless, it is intriguing that the heterologous overexpression of At-rGRF3 in B. oleracea resulted in longer roots than the wild type (63).…”
Section: Regulatory Roles In Root Growth and Developmentmentioning
confidence: 99%
“…Liu et al found that transgenic miR396 -overexpressing plants are more tolerant to drought than wild-type plants in Arabidopsis [53]. In particular, the AtGRF3 transgene yielded an increase in leaf size under mild drought stress and showed enhanced resistance to certain plant pathogens [54]. Further analysis revealed that Sp-miR396a-5p transcription levels are up-regulated under salt and drought stresses, and additionally, the expression of Sp-miR396a-5p is down-regulated under pathogen-related biotic stress [55], and the relevant link between salt and alkali stress of osa-miR396c in rice was established by Gao et al [56].…”
Section: Discussionmentioning
confidence: 99%